Parental Use of Taboo Words and its Impact on Adolescent Behavior - Nabillah Putri, Shania; Aqilah Nisa, Cinta (Jurnal Pendidikan Tambusai, 2025)
This study investigates the emotional, cognitive, and behavioral impact of taboo words spoken by parents to their children, with a specific focus on young adults aged 19-25. Through interviews with nine participants, 15 taboo expressions and seven social comparison phrases were identified and semantically categorized based on Jay’s (2009) classification into five categories: mental, physical, religious, scatological, and sexual terms. The findings reveal that mental terms, such as insults targeting intelligence, were the most frequently used, accounting for 8 occurrences. The use of social comparison, particularly upward comparison, further exacerbated feelings of inadequacy and low self-esteem in the participants. This study emphasizes the long-term psychological impact of parental language, urging parents to be more mindful of the words they use to foster healthier emotional development and stronger parent-child relationships. The results suggest that frequent exposure to derogatory language can lead to negative coping mechanisms, emotional dysregulation, and anxiety, highlighting the importance of supportive and constructive communication within families.